Invasiveness of Pomacea canaliculata: the differences in life history traits of snail populations from invaded and native areas - Zhang, Chunxia (2023)
Pomacea canaliculata is native to South America and has become a widely distributed agricultural and environmental pest in southern China. Previous studies have primarily focused on the tolerance of P. canaliculata to various environmental factors, and compared non-native invasive P. canaliculata with natives or non-invasive congeners. However, there has been no research concentrated on variation in innate growth and reproductive characteristics between P. canaliculata in its native and invaded areas. To address this gap, we conducted the first comparison experiment between P. canaliculata from their native area (Argentina) and from an invaded area (China). We recorded the temporal dynamics of shell height of male and female P. canaliculata, and investigated the sexual maturation and egg-related indicators in two populations from each country, rearing them under homogeneous temperature, photoperiod and food conditions. Our results showed that the shell growth rate of P. canaliculata in Argentina was significantly lower than that of P. canaliculata in China. Moreover, P. canaliculata exhibited stronger reproductive characteristics in populations from China, mainly reflected in the earlier sexual maturity, larger egg masses, higher hatching success, and a trend of shorter incubation period. These differences probably arose due to contemporary evolution in invaded areas under strong selective pressures in rice fields, and, together with more favorable climates, enable the snail populations to rapidly grow and expand in southern China.